The Human Rights Violation in India's Hijab Ban and the Need for Community Advocacy - Gunawan, Yordan; Mulloh, Ahmad Fahmi Ilham; Syamsu, Andi Pramudya; Manuel Beltrán Genovés (Yuridika, 2024)
The Karnataka state government banned the hijab in schools on February 5, 2022, and several women petitioned the Karnataka High Court to overturn it. A panel of three judges concluded on March 15, 2022, that the hijab is not an important Islamic practice. By punishing females for their wardrobe choices, the court stressed conformity above girls' access to education. The hijab prohibition is part of a pattern of discrimination against Muslim women that violates their human rights. With the rise of authoritarianism, a new form of feminism is emerging in which Muslim girls in India are challenging the authorities and resisting asserting their identity and preferences. Previous research has described human rights violations experienced by Indian female students regarding court decisions. Therefore, the purpose of the research is to investigate the human rights violations that have been disclosed as a result of India's hijab ban which employs normative juridical research methodologies. The method refers to a legal research approach that involves the examination of written law from multiple perspectives. The High Court's verdict worsens Muslim girls and women's education-related harassment, trauma, and prejudice. Muslim students removing their hijabs and burqas before entering schools is a difficult topic that requires neutrality. The verdict would affect the Indian Constitution and the Muslim population, especially hijab-wearing women. United Nations (UN) Women has backed all initiatives of India's Ministry of Women and Child Development that seek to advocate for those affected by the hijab ban to promote gender equality and prevent discrimination against women.